The Influence of The Application of Pairs Check Technique (PCT) Towards Students’ Writing Ability at Grade Ten of SMA Catur Karya Tulang Bawang 2014 - Siti Nuryati (Bandar Lampung University (UBL), 2014)
This is an experimental research that aimed to find out the influence of the application of pairs check technique towards students’ writing ability at grade ten of SMA Catur Karya Tulang Bawang2014. Pairs check was applied to increase the students’ ability in writing that isstill lack. Data were collected by incorporating two pre-tests and two post-tests in experimental group and control group. In experimental group,the treatmentwas given by using pairs check technique while control group received traditional teaching (TT). Data analysis was attempted using t-Test for two group design. The resultindicated that p-value 1% = 2,04 and 5% = 2,75while t-value = 5, 58. It means p-value is smaller than t-value. Hence, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The researcher concluded that the application of using pairs check technique was more effective than traditional teaching to improve students’ ability in writing.